THE RELATION OF BODY MASS INDEX WITH CARDIOVASCULAR ENDURANCE DAN AGILITY OF FOOTBALL PLAYER - Prihatini, Agus Dwi; widodo, achmad (Jurnal Kesehatan Olahraga, 2019)
Football is a sport that requires a relatively long time, to support good play in addition to excellent physical condition soccer players must have an ideal body mass index and cardiovascular endurance and good agility so that they can receive and carry out training programs that have been determined by the trainer and can complete the targets given as well as possible and get optimal results in each match he faces. This study aims to determine the relationship of body mass index with cardiovascular endurance and agility of Pre-Porprov soccer players in Mojokerto Regency. This research is a quantitative associative study with a sample of 18 senior age people, 17-17 years old and male sex. The data obtained in this study are weight, height to find out the body mass index, to determine the condition of cardiovascular endurance multystage fitness test with the standard operating procedures that have been determined and to determine the condition of agilitytest arrowhead agility drill test with predetermined standard operational procedures. Data analysis used in this study is Pearson Correlation with the results of the analysis obtained stating that there is a significant relationship between body mass index with cardiovascular endurance resulting in a strong unidirectional correlation of r value of -0.601 with an explanation if the body mass index value is high hence the lower the value of cardiovascular endurance of soccer players, as well as the results of agility data analysis which states that there is a significant relationship between body mass index and agility resulting in a strong correlation in the same direction from the r value of 0.629 with an explanation of the player's body mass index value football is the higher the time value of agility on soccer players. Keywords: Body Mass Index, Cardiovascular Endurance, Agility.